Maternal Magnesium Sulphate Exposure Predicts Neonatal Magnesium Blood Concentrations. (11th December 2013) - Sherwin, Catherine M.T.; Balch, Alfred; Campbell, Sarah C.; Fredrickson, Jeunesse; Clark, Erin A.S.; Varner, Michael; Stockmann, Chris; Korgenski, E. Kent; Bonkowsky, Joshua L.; Spigarelli, Michael G.
Abstract Tocolytic use of magnesium sulphate is associated with excess neonatal mortality and has been proposed to follow a dose–response relationship. This study aimed to define the correlation between maternal and neonatal magnesium blood concentrations. Magnesium blood concentrations were retrospectively obtained for mother–neonate pairs who were cared for at an Intermountain Healthcare facility from January 2009 to October 2011. Complete data were available for 231 mother–neonate pairs. Mean (±SD) maternal and neonatal magnesium concentrations were 5.43 ± 1.69 and 2.98 ± 0.94 mg/dL, respectively. Maternal and neonatal magnesium concentrations were highly correlated (p < 0.001). In univariate analyses, residual unexplained variability was high (r2 = 0.19). However, further multivariate analyses revealed that caesarian section, severe pre‐eclampsia and Apgar score at 5 min. were significantly associated with neonatal magnesium concentrations (p < 0.05 for all). Maternal magnesium concentrations correlate with neonatal exposure. This finding suggests that maternal monitoring deserves further evaluation as a marker of foetal toxicity.